Baseline HBsAg quantitative and CD4 T cell counts are associated with HBsAg loss in people living with HIV/HBV coinfection after combined antiretroviral therapy - Xia, Muye; Zhao, Yuhang; Yu, Tao; Lin, Xiaoli; Liao, GuiChan; Jiang, Yuanhui; Mao, Jingchun; Peng, Jie; Cai, Shaohang (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAchieving Hepatitis B surface antigen (HBsAg) loss is a significant goal for chronic hepatitis B patients. This study aims to evaluate HBsAg loss in individuals with HIV/HBV coinfection and explore the association of clinical variables with this outcome.MethodsWe enrolled 138 individuals coinfected with HIV/HBV and 480 HBV mono-infected individuals who initiated antiviral treatment. We employed Kaplan-Meier analysis to compare the rate of HBsAg loss between individuals with HIV/HBV coinfection and those with HBV mono-infection. In the HIV/HBV coinfected cohort, we used Cox proportional hazards models to assess the association between various factors and the incidence of HBsAg loss.ResultsThe cumulative HBsAg loss rate was higher among HBV/HIV coinfected individuals (13 patients, 11.5% at year 3) compared to HBV mono-infected individuals (1 patient, 0.6%) after antiviral therapy. In the HIV/HBV coinfected cohort, the multivariable analysis revealed that lower baseline HBsAg level (HR 0.53; 95% CI 0.38-0.74, p<0.001) and baseline CD4 T cell counts < 180 cells/uL (HR 0.32; 95% CI 0.10-0.96, p=0.042) were associated with an increased indicator of HBsAg loss. Additionally, the receiver-operating characteristic curve analysis indicated an area under the curve of 0.771 for baseline HBsAg levels and 0.758 for baseline CD4 cell counts at year 1 in predicting HBsAg loss.ConclusionsAfter antiretroviral therapy, HIV/HBV coinfected adults achieve higher rates of HBsAg loss. Baseline HBsAg quantitative and CD4 T cell counts are associated with HBsAg loss in individuals with HIV/HBV coinfection after combined antiretroviral therapy and may inform treatment decisions.